Pengaruh Induksi Timbal (Pb) Pada Mencit (Mus musculus) Terhadap Kadar Hemoglobin - Liah Kodariah; Baiq Isti; Hasanah Sanusiyah Harahap; Reyna Synthia (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2023)
Hemoglobin is the oxygen-carrying compound in red blood cells. A low hemoglobin content indicates severe anemia this is due to pregnancy and the presence of heavy metals such as Lead (Pb). Lead Pb that enters through the respiratory tract and digestive tract will absorbed through the gastrointestinal tract and distributed to other tissues via blood. This study aims to determine Hb levels in the blood of mice (Mus Musculus) exposed to lead. This research method is experimental using 25 male mice which divided into 5 groups, namely the control group and the treatment group with the administration of Pb acetate by oral route for 1 week, 2 week, 3 weeks, and 4 weeks. The sample taken is the blood of mice obtained from heart to be checked for hemoglobin levels according to the time of exposure. The results of this study obtained hemoglobin levels in the P1 group of 11,2 g/dL and the P2 group of 10,078 g/dL, the Hb value includes into the category of very mild anemia. While the P3 group was 8,16 g/dL and the P4 group of 7,54 g/dL including the category of mild anemia. On the control group of 12,82 g/dL was included in the Normal Hemoglobin. Based on the result of the study, it can be concluded that giving exposure to Lead Pb to mice (Mus Musculus) has an effect on decreasing levels of Hb.